The Role of Practice in Gnoseological Researches of Academic Philosophical Culture Representatives of the 1960s in Ukraine - Чуйко, Настасія Вадимівна (Київський національний університет імені Тараса Шевченка, 2025)
The paper presents a historical-philosophical reconstruction of the role of practice in the gnoseological studies of representatives of academic philosophical culture in Ukraine during the 1960s, with a particular emphasis on the Kyiv School of Philosophy. Employing a descriptive approach, it was revealed that in the gnoseological framework of the Kyiv School, practice functions not only as the purpose and criterion of truth but also as a factor that restricts the range of properties of the object under investigation taken into account to characteristics that adequate to the current practical needs, thereby directing human thinking. The conception of knowledge as conditioned by practice led some Kyiv scholars to interpret logical forms of thinking as products of socio-historical practical activity rather than direct reflections of reality. An examination of the continuity between the epistemological developments of the 1960s and the subsequent worldview-oriented studies of the 1970s suggests that the proposition of the limiting function of practice in cognition was further elaborated in a reinterpretation of the notion of the world as intrinsically linked to practice. Understanding cognition as a theoretical world mastery that precedes the practical and necessarily presupposes the inclusion of human attitude toward the world resulted in the identification of philosophy's worldview function, and laid the intellectual groundwork for establishing the worldview-anthropological research orientation in Ukraine's academic philosophical culture during the 1970s.

Здійснено історико-філософську реконструкцію ролі практики для гносеологічних студій представників академічної філософської культури в Україні 1960-х років, зокрема – у межах Київської школи філософії. Застосовуючи дескриптивний підхід, було виявлено, що практика в гносеології Київської школи виконує роль не лише мети та критерія істинності, але й обмежує множину властивостей досліджуваного об’єкта до адекватних практичним потребам людини ознак, чим спрямовує її мислення. Розуміння мислення як обумовленого практикою привело деяких київських дослідників до трактування його логічних форм як продуктів суспільно-історичної практичної діяльності, а не безпосереднього відображення дійсності. Простеження зв’язку між гносеологічними розробками 1960-х років і подальшими світоглядними студіями 1970-х дозволило зробити висновок, що положення про обмежуючу функцію практики для пізнання мало розвиток у специфічному тлумаченні поняття світу як пов’язаного з практичною діяльністю, а трактування пізнання як теоретичне освоєння дійсності, що необхідно передує практичному та передбачає включення ставлення людини до світу у розгляд буття, мало наслідком виокремлення світоглядної функції філософії, підготувавши ґрунт для становлення світоглядно-антропологічного напрямку досліджень в академічній філософській культурі України у 1970-х роках.
Роль практики у гносеологічних студіях представників академічної філософської культури в Україні 1960-х років
Keywords: academic philosophical culture in Ukraine during the second half of the 20th century in the Soviet era; Kyiv School of Philosophy; gnoseology; practice; world mastery; worldview; академічна філософська культура в Україні другої половини ХХ століття радянської доби; Київська школа філософії; гносеологія; практика; освоєння світу; світогляд